HOUSE PRICES AND THE MACROECONOMIC ENVIRONMENT IN TURKEY: THE EXAMINATION OF A DYNAMIC RELATIONSHIP - Ozan Yıldırım, Mustafa; İvrendi, Mehmet (Economic Annals, 2017)
The aim of this paper is to examine the dynamic relationship between house prices, income, interest rates, housing permits, and share prices in Turkey, using Structural Vector Autoregressive (SVAR) models. This paper uses both monthly and quarterly data for the Turkish economy and applies four different SVAR models to reveal this dynamic relationship over the 2003–2016 period. The results show statistically significant and substantial relationships between the variables. The analysis also shows that house prices and housing permits as housing market variables are very sensitive to monetary policy and income shocks. The key finding of the study for policymakers is that a change in mortgage rates is the factor that most changes house prices. The study also shows that the housing market plays an important role in transferring monetary policy to the real economy in Turkey